A new framework for ground motion selection for structural seismic assessment. (15th June 2023) - Li, Cuihua; Kunnath, Sashi K.; Zhao, Yingfang
Highlights: A novel approach is proposed to select ground motions for structural dynamic analyses. The proposed approach combines the merits and overcomes the challenges of conventional methods. The target to be matched is the mean and covariance of T 0, T g, β max and γ conditioned on the design PGA. PGV/PGA is added as the second conditional parameter to consider pulse-like effects. The pros and cons of the UHS and CMS-based methods are thoroughly examined. The proposed approach is compared to the CS method with illustrative example. The proposed approach considers the spectral shape and spectral variability of realistic ground motions while avoiding the choice of the conditioning period. Abstract: Performance-based structural seismic assessment generally requires the selection of ground motions wherein the target acceleration response spectrum ( S a) should be matched in a desired period range. The pros and cons of the commonly used uniform hazard spectrum (UHS), conditional mean spectrum (CMS) and conditional spectrum (CS) are thoroughly examined. Aiming at combining the merits and overcoming the challenges of these methods, a new framework is proposed to construct a series of conditional target spectra for selecting ground motions. The response spectrum is expressed as the product of peak ground acceleration ( PGA ) and the normalized spectra ( β  =  S a/ PGA ) which can be smoothed by four spectral shape parameters. The proposed framework provides the expected median and covariance of the spectral shape parameters conditioned on specified design values of PGA and PGV / PGA (peak ground velocity/ PGA ) . Efficient step-by-step procedures are developed for the application of the proposed alternative approach, and a sample application is illustrated and compared with the CS approach. It is demonstrated that the proposed methodology is capable of incorporating conventional probabilistic seismic hazard analysis (PSHA), considering spectral shape and spectral variability of realistic ground motions while avoiding the choice of the conditioning period. Site class effects can also be incorporated into the proposed approach.